Beliefs and values in Japanese acupuncture: an ethnography of Japanese trained acupuncture practitioners in Japan - Benjamin Chant; Jeanne Madison; Paul Coop; Gudrun Dieberg (Integrative Medicine Research)
Background: Japanese acupuncture is gaining international recognition. However, previous research has failed to comprehensively describe the characteristics of Japanese acupuncture by not investigating it within the Japanese clinical environment. This study aimed to identify unique and routine elements of Japanese acupuncture, describe these elements in detail, and examine how the current beliefs and attitudes of Japanese acupuncture practitioners related to philosophical concepts in their practice. Methods: Between August 2012 and December 2016, ethnographic fieldwork was conducted in Japan. Japanese trained acupuncture practitioners were recruited by chain referral and emergent sampling. Data were collected through participant observation, interviews, and by analyzing documents. Thematic analysis was used to critically evaluate the data. Results: Thirty-eight participants were recruited. Of these participants, 22 agreed to clinical observation; 221 treatments were observed with 172 patients. Additionally, 17 participants consented to participate in formal semistructured interviews and 28 to informal unstructured interviews (fieldwork discussion). Besides “knowledge,” “beliefs and values” was a major theme interpreted from the data. Subthemes—including Zen Buddhism, effect through technique, instant effects of treatment, anatomical areas of significance, resolution of abnormalities, minimal stimulation, and patient comfort and customer service—were identified. Conclusion: Beliefs and values are an underrepresented, yet extremely important aspect of philosophical concepts influencing acupuncture practice in Japan. Uniquely Japanese beliefs and values that do not rely on a commitment to any spiritual or religious affiliations or proprietary knowledge of traditional or biomedicine may be successfully exported from Japan to advance acupuncture education, research and practice in international contexts.